2013
DOI: 10.1021/jo400344m
|View full text |Cite
|
Sign up to set email alerts
|

Primary Amines as Directing Groups in the Ru-Catalyzed Synthesis of Isoquinolines, Benzoisoquinolines, and Thienopyridines

Abstract: Isoquinolines, benzoisoquinolines, thieno[3,2c]pyridines and fused heteroaryl[2,3-c] pyridines, with a wide variety of substituents at different positions of the aromatic or heteroaromatic rings, have been synthesized by Ru-catalyzed oxidative coupling of a broad range of benzylamines or heterocycles with internal alkynes. All benzylamines and heterocycles have unprotected primary amines as efficient directing groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(42 citation statements)
references
References 91 publications
6
36
0
Order By: Relevance
“…These substrates were selected to cover a wide scope of structural situations. The initial reaction conditions were as described in our previous report 15…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These substrates were selected to cover a wide scope of structural situations. The initial reaction conditions were as described in our previous report 15…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that the coupling of 1 a (1 mmol) with 2 a (2 mmol) catalyzed by [{Ru(η 6 ‐cymene)(μ‐Cl)Cl} 2 ] (0.1 mmol) in the presence of Cu(OAc) 2 (1 mmol) and K[PF 6 ] (0.1 mmol) in methanol at 100 °C for 24 hours affords benzo[ h ]isoquinoline 3 aa in 85 % yield 15. A short screening of the reaction conditions showed that both the solvent MeOH and the oxidant Cu(OAc) 2 were the optimal choices.…”
Section: Resultsmentioning
confidence: 99%
“…Unprotected primary amines serve as efficient directing groups in the cationic ruthenium(II)-catalyzed oxidative coupling of various benzylamines or heteroarylmethylamines with internal alkynes (Eq. (7.40)) [49]. A variety of isoquinolines, benzoisoquinolines, and fused heteroaryl[2,3-c] pyridines were generated from this catalytic C-H functionalization process.…”
Section: Cyclization With Carbon Monoxidementioning
confidence: 99%
“…Benzoisoquinolines ( Figure 1) are relatively unexplored heterocycles which have attracted limited interest in the literature [1][2][3][4][5][6][7][8]. Benzo[f]isoquinolines 1 [1][2][3][4] are useful in the synthesis of aza-steroids [3] and have had their affinity for the 5-HT3 receptor explored [4].…”
Section: Introductionmentioning
confidence: 99%
“…Benzo[f]isoquinolines 1 [1][2][3][4] are useful in the synthesis of aza-steroids [3] and have had their affinity for the 5-HT3 receptor explored [4]. Benzo[h]isoquinolines 2 have also been synthesized [5][6][7][8] and some of these have been shown to be potent inhibitors of ATP-competitive Chk1 kinase [8]. The benzo[g]isoquinoline nucleus 3 has also been reported [8].…”
Section: Introductionmentioning
confidence: 99%